Reconstruction of landslide movements by inversion of 4‐D electrical resistivity tomography monitoring data. Issue 3 (13th February 2016) - Wilkinson, Paul; Chambers, Jonathan; Uhlemann, Sebastian; Meldrum, Philip; Smith, Alister; Dixon, Neil; Loke, Meng Heng
Abstract: Reliable tomographic inversion of geoelectrical monitoring data from unstable slopes relies critically on knowing the electrode positions, which may move over time. We develop and present an innovative inverse method to recover movements in both surface directions from geoelectrical measurements made on a grid of monitoring electrodes. For the first time, we demonstrate this method using field data from an active landslide to recover sequences of movement over timescales of days to years. Comparison with GPS measurements demonstrated an accuracy of within 10% of the electrode spacing, sufficient to correct the majority of artifacts that would occur in subsequent image reconstructions if incorrect positions are used. Over short timescales where the corresponding subsurface resistivity changes were smaller, the constraints could be relaxed and an order‐of‐magnitude better accuracy was achievable. This enabled the onset and acceleration of landslide activity to be detected with a temporal resolution of a few days. Key Points: ERT monitoring of landslides requires knowledge of electrode movements that can be costly to obtain An inverse method can be used to reconstruct electrode movements from geoelectrical monitoring data First field demonstration of ERT time‐lapse movement inversion over timescales of days to years